The Impact of Green Accounting, Environmental Disclosure, and Material Flow Cost Accounting on Corporate Profitability - Aisyah, Salma Putri; Kurniawati, Lintang (Dinasti International Journal of Economics, Finance & Accounting, 2026)
Environmental sustainability issues require companies—particularly those in the consumer sector that contribute to environmental degradation—to focus not only on financial performance but also on environmental impacts, thereby driving the adoption of green accounting, environmental disclosure, and MFCA as approaches to sustainability accounting. This study aims to empirically test the influence of green accounting, environmental disclosure, and Material Flow Cost Accounting (MFCA) on the profitability of consumer sector companies listed on the Indonesia Stock Exchange for the period 2019–2023. This study uses a quantitative approach with a sample of 40 companies (185 observations) selected through purposive sampling based on specific criteria. The research data consists of secondary data obtained from companies’ annual reports and sustainability reports, which were then analyzed using SPSS through classical assumption tests, multiple linear regression, the coefficient of determination (R²), as well as F-tests and t-tests to examine the simultaneous and partial effects of the independent variables on profitability. The research results indicate that Green Accounting does not have a significant effect on profitability (t = 0.594; sig = 0.553), whereas Environmental Disclosure (t = −1.766; sig = 0.079) and MFCA (t = −5.097; sig = 0.001) have a significant negative effect on ROA. These findings indicate that sustainability practices have not yet had a direct impact on improving profitability because they still incur short-term implementation costs, although they have the potential to improve long-term efficiency and performance.